Draft Annual Plan 2006-2007 Planning and Development Department Government of Jharkhand - Planning Commission (Planning Commission, 2006)
Jharkhand ""The Land of Forest"" is one of the newly established States of Indian Union carved out of the State of Bihar in November 2000. Its undulating plateau is characterized by tropical forests and tribal settlements with abundant natural resources which need to be utilized in a sustainable manner for overall development of the State. Cereal crops like paddy and maize occupy a major portion of the agricultural area in the stale with pulses like black gram and red gram coming next to it. Other important crops grown arc wheat, oilseeds and minor millets. Vegetable production is high in certain pockets of the State placing it at a comfortable position compared to other States
Planning and Development Department Government of Jharkhand